SIZING OPTIMIZATION. - Alfredo Soeiro (1987)
A method for structural member sizing optimization to be used for designing planar frames is presented. The procedure is based on the Augmented Lagrangian Multiplier method. The algorithm includes the displacements as state variables and consequently combines the analysis and the search for the optimal section properties into a single step. This combination process avoids the usual cycling between analysis and optimization phases. The width and height of rectangular elements are chosen from a finite compact set. The static equilibrium equations are treated as equality constraints eliminating the need to solve the standard structural analysis problem. The method handles displacement and stress limits as inequality constraints. Comparisons of performance and results are made with other optimization techniques.